A Missing Step: The Efficiency of Psychological Mindedness Training During Psychiatry Residency - Mark Cogburn; Nahrain Raihan; Hannah Scott; Hannah Cogburn (Recent Updates in Disease and Health Research Vol. 7, 2024)
Psychiatry house officers, who lack psychological mindedness, struggle to understand the multiple determinants of behavior, or the numerous meanings of a single symptom. This is unfortunate because most psychiatry resident interns feel that they are finally among the group where they belong…like-minded physicians who share a fascination with human nature and a desire to grasp all the nuances and complexities of human behavior. This paper provides a framework for psychiatry departments to train residents along a continuum of psychological mindedness. Each Psychiatry resident should initially complete the 21 items. For residents who score below 10, the supervisor should consider having the resident complete the Psychological Perspective Taking and Empathic Concern Scales on the Interpersonal Reactivity Index. The intended goal of this intervention is to acknowledge that all scores, low and high, are helpful in regard to training psychiatric residents. The authors explain the concept of psychological mindedness, explore the pros and cons of acquiring psychological mindedness, and a scientific basis for its use in general psychiatry. A new model is included to capture any resident’s ability to become psychologically minded, with direction for Program directors to possibly develop growth in a resident’s psychological mindedness over four years of training.